The Effect of Antioxidants on Sperm Quality Parameters and Pregnancy Rates for Idiopathic Male Infertility: A Network Meta-Analysis of Randomized Controlled Trials - Li, Kun-peng; Yang, Xue-song; Wu, Tao (Frontiers in Endocrinology, 2022)
Purpose: Male infertility is a global public health issue recognized by the WHO. Recently, antioxidants are increasingly used to treat idiopathic male infertility. However, the lack of available evidence has led to the inability to rank the effects of antioxidants on the sperm quality parameters and pregnancy rate of infertile men. This network meta-analysis studied the effects of different antioxidants on sperm quality and pregnancy rate of idiopathic male infertility. Methods: We searched Pubmed, Embase, Web of science and Cochrane Library database for randomized controlled trials (RCTs). The weighted mean difference (WMD) and odds ratio (OR) were applied for the comparison of continuous and dichotomous variables, respectively, with 95 % confidence intervals. The outcomes were sperm motility, sperm concentration, sperm morphology and pregnancy rate. Results: A total of 23 randomized controlled trials with 1917 patients and 10 kids of antioxidants were included. L-carnitine, L-carnitine + L-acetylcarnitine, coenzyme-Q10, ω-3 fatty acid and selenium were more efficacious than placebo in sperm quality parameters. L-carnitine was ranked first in sperm motility and sperm morphology (WMD 6.52% [95%CI:2.55% to 10.05%], WMD 4.96% [0.20% to 9.73%]). ω-3 fatty acid was ranked first in sperm concentration (WMD 9.89×106/ml, [95%CI:7.01 to 12.77×106/ml]). In terms of pregnancy rate, there was no significant effect compared with placebo. Conclusions: L-carnitine was ranked first in sperm motility and sperm morphology. ω-3 fatty acid was ranked first in sperm concentration. Coenzyme-Q10 had better effective treatment on sperm motility and concentration. Furthermore, high-quality RCTs with adequate sample sizes should be conducted to compare the outcomes of different antioxidants.